The market, the state, and the Export-Import Bank of the United States, 1934-2000 - Becker, William H. (Cambridge University Press, 2003)
This is the first history of the Export-Import Bank of the United States (Ex-Im) based on archival sources. Ex-Im has played a part in all of the major events that marked the growing involvement of the United States in the international economy.